Assessment of the bonding quality of Toona ciliata (Australian cedar) lamellas for glulam beams produced with different adhesives and surface finishes - Oliveira, Karina Aparecida de [UNESP]; Jardim, Pedro Ignacio Lima Gadelha; Oliveira, Carolina Aparecida Barros [UNESP]; Rodrigues, Edson Fernando Castanheira; Christoforo, André Luis; Molina, Julio Cesar (Elsevier, 2025)
Glued laminated timber (Glulam) is an engineered structural product manufactured based on quality control. Although its production is generally carried out with pine and eucalyptus species, scientific studies have dedicated time to investigate the possibility of using other species from reforestation. Although some species of Australian cedar have been studied, the Toona ciliata has not yet been applied for the production of glulam. In addition to timber selection, the specification of adhesive used to glue lamellas that does not emit formaldehyde has also aroused the interest of researchers. For this purpose, two-component polyurethane adhesive based on vegetable oils has been presented as a potential alternative for resorcinol-formaldehyde, which is commonly used in the glulam manufacturing. In addition, it was also noticed that execution of surface finish (sanding) on lamellas has not been target of researches concerning gluing performance. Therefore, the purpose of this study was to evaluate the effect of different combinations of adhesive (two-component polyurethane and resorcinol-formaldehyde) and finishing (planing and sanding with 80-, 120- and 220-grid) on delamination and shear strength of glue line between Australian Cedar lamellas. All adhesive-finish combinations presented some percentage of delamination within the limit permitted for hardwoods (ABNT NBR 7190–6). The predominant mode of rupture was wood failure, which highlights the potential for using Australian Cedar timber and vegetable oil-based adhesive in the production of glulam elements.
Keywords: Bond quality; Delamination; Finishing; Glulam; Sher strength; Surface roughness; Toona ciliata